Respuesta :

Answer:

Explanation:

1).  Ca(NO₃)₂ + KI → CaI + K(NO₃)₂

    This equation is incorrect.

    When Ca⁺⁺ reacts with I⁻, final product is CaI₂

    And when K⁺ react with NO₃⁻, final product is KNO₃

    Hence the equation will be,

    Ca(NO₃)₂ + KI → CaI₂ + KNO₃

    Now we have to balance this equation.

     Ca(NO₃)₂ + 2KI → CaI₂ + KNO₃

                          ↓

     Ca(NO₃)₂ + 2KI → CaI₂ + 2KNO₃

2). Ca(NO₃)₂ + KOH → CaOH + K(NO₃)₂

    This equation is incorrect,

    Since the reaction of Ca⁺⁺ with OH⁻ gives the final product     Ca(OH)₂

    And final product of K⁺ and NO₃⁻ is KNO₃

    Therefore, the equation will be,

    Ca(NO₃)₂ + KOH → Ca(OH)₂ + KNO₃

    Now we will balance this equation by changing the coefficients of the      molecules until the number of atoms on both the sides become equal.

    Ca(NO₃)₂ + KOH → Ca(OH)₂ + 2KNO₃

                                ↓

     Ca(NO₃)₂ + 2KOH → Ca(OH)₂ + 2KNO₃

3). Ca(NO₃)₂ + Na₂C₂O₄ → CaC₂O₄ + 2Na(NO₃)₂

    This equation is incorrect,

    Since the reaction of Na⁺ and NO₃⁻ gives the final product    NaNO₃.

    Therefore, the correct equation will be,

    Ca(NO₃)₂ + Na₂C₂O₄ → CaC₂O₄ + 2NaNO₃

     This equation is in the balanced form.

ACCESS MORE